Evolution of acute chronic obstructive pulmonary disease treated with non-invasive ventilation - Navarro RodrÃguez, Zadis; Romero Garcia, Lázaro Ibrahim; Guzman Perez, Niger; Brito Laserra, Franklin (MEDISAN.., 2020)
Introduction: Non-invasive ventilation is a new modality of respiratory support therapy in patients with acute chronic obstructive pulmonary disease. Objective: To describe the factors related to failure of non-invasive ventilation treatment in the population of patients with exacerbated chronic obstructive pulmonary disease. Methods: An observational, descriptive and cross-sectional study was carried out in the intensive care units of Saturnino Lora Hospital, between January, 2011 and January, 2019. Results: The presence of leaks, the start time of the treatment longer than 24 hours, the decrease in the average values of pH and Glasgow, the increase in respiratory and heart rates and PaCO2, are associated with failure of non-invasive ventilation. Conclusions: Alterations of typical clinical and hemogasometric variables of ventilation, structure the failure in this patients population.